المشكلات اللغوية التي تواجه طلاب كليات الالهيات في تركيا في تعليم اللغة العربية Türkiye’deki İlahiyat Fakültesi Öğrencilerinin Arapça Öğretiminde Karşılaştığı Dilsel Problemler - Acat, Yaşar (Şırnak Üniversitesi, 2016)
Arabic is a language that has gained importance with the influence of external factors. Religious dimension comes first among these factors. The Qur’an, which non-Arabic Muslims believed strongly as much as Arabic Muslims, was revealed in Arabic and The Prophet used this language to address his Ashâb (companions). Arabic and non-Arabic Muslims concentrated on Arabic, the language of Islam, even more in order to better understand the Qur’an and the Sunnah (the tradition of The Prophet). h teaching Arabic are divided into two parts as non-linguistic and linguistic. While nonlinguistic difficulties often stand for problems related to students, teachers, textbooks, classroom environment and teaching methods; linguistic difficulties stand for the difficulties in reading, writing, and understanding as well as phonological, morphological, and syntactic ones. The degree of the difficulties that arise from the very language itself can depend on the societies where the Arabic language is not spoken as the mother tongue. The issue we will be examining in this article is the difficulties that arise from this language itself and reasons of them, as well as solutions and proposals to those problems. This study aims to develop language skills of the students of Theology as well as reaching to a better language teaching.
Keywords: Arabic; Teaching Arabic as a foreign language; Problems faced in the language teaching; Solutions